2014
DOI: 10.1080/08941920.2014.918233
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Stakeholder Values into Climate Risk Management Programs: Decision Aiding for REDD in Vietnam

Abstract: The United Nations (UN) Reducing Emissions from Deforestation and Forest Degradation (REDD) program offers incentives for developing countries to reduce CO 2 emissions and to invest in low-carbon paths to sustainable development. In designing and deploying REDD programs, the UN is asking that participating nations go beyond focusing just on technical issues associated with carbon management and also include a range of social considerations; for example, program managers are being asked to undertake stakeholder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…2, of active decision-support approaches. Based on our own experiences with these approaches (e.g., Arvai and Campbell-Arvai 2013;Arvai et al 2014;Arvai and Post 2012;Bessette et al 2014;Kenney et al 2015), we believe strongly that asymmetric interventions should not be applied until those engineering the decision-making environment have a clear sense of the personal, societal, or environmental objectives that they are trying-and, importantly, that decision-makers wish-to meet (Smith et al 2013). In this light, we feel that a deliberative and transparent approach to identifying and implementing defaults and other nudges (including addressing potential trade-offs between autonomy and benefits to individuals and society) will go a long way to addressing ethical concerns relating in particular to consumer autonomy and welfare (Spotswood et al 2012).…”
Section: Experiments 3: Environmentally Friendly Food Choicesmentioning
confidence: 99%
“…2, of active decision-support approaches. Based on our own experiences with these approaches (e.g., Arvai and Campbell-Arvai 2013;Arvai et al 2014;Arvai and Post 2012;Bessette et al 2014;Kenney et al 2015), we believe strongly that asymmetric interventions should not be applied until those engineering the decision-making environment have a clear sense of the personal, societal, or environmental objectives that they are trying-and, importantly, that decision-makers wish-to meet (Smith et al 2013). In this light, we feel that a deliberative and transparent approach to identifying and implementing defaults and other nudges (including addressing potential trade-offs between autonomy and benefits to individuals and society) will go a long way to addressing ethical concerns relating in particular to consumer autonomy and welfare (Spotswood et al 2012).…”
Section: Experiments 3: Environmentally Friendly Food Choicesmentioning
confidence: 99%
“…Information needs to be shared proporsionally and consistent during the projects. Stakeholder involved needs to have opportunity to exchange information, improve transparency [20] and understanding the vision between stakeholder; Outline the engagement that required from each stakeholders involved in the sustainable natural resource management. Based on the process of stakeholder engagement in two socioeconomic research project, we found that there are some factors affecting stakeholder engagement: effective communication, hence the stakeholder will pay more attention and time about what is the project, the purposes and what kind of thing that they can do to support the support in managing natural resource sustainably.…”
Section: Sustainable Natural Resource Managementmentioning
confidence: 99%
“…Another increasingly popular class of mitigation strategies focuses on increasing sinks of carbon from the atmosphere by enhancing land-based and oceanic carbon uptake. A number of natural strategies have received serious attention from researchers and policy-makers including changing agricultural practices to increase carbon retentionsuch as no-till agriculture (Lal et al, 2004) -as well as discouraging deforestation, and incentivising reforestation, via economic or policy levers (Kenney et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%